2009
DOI: 10.1002/hep.22960
|View full text |Cite
|
Sign up to set email alerts
|

Apolipoprotein B100 acts as a molecular link between lipid-induced endoplasmic reticulum stress and hepatic insulin resistance #

Abstract: Accumulation of unfolded and misfolded proteins in the endoplasmic reticulum (ER) results in ER stress and lipid overload-induced ER stress has been implicated in the development of insulin resistance. Here, evidence is provided for a molecular link between hepatic apolipoprotein B100 (apoB100), induction of ER stress, and attenuated insulin signaling. First, in vivo upregulation of hepatic apoB100 by a lipogenic diet was found to be closely associated with ER stress and attenuated insulin signaling in the liv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
91
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(94 citation statements)
references
References 35 publications
3
91
0
Order By: Relevance
“…Su et al proposed that, in hepatocytes, OA induces ER stress by increasing the translocation of newly synthesized apoB into the secretory pathway and, thus, the amount of apoB processed by the ER ( 9 ). On the basis of on our prior studies, we can rule out increases in lipid peroxides and reactive oxygen species as the mechanism for OA-induced ER stress ( 14 ).…”
Section: Dha But Not Oa or Pa Increases Autophagic Fl Ux In Mca Cellsmentioning
confidence: 80%
See 1 more Smart Citation
“…Su et al proposed that, in hepatocytes, OA induces ER stress by increasing the translocation of newly synthesized apoB into the secretory pathway and, thus, the amount of apoB processed by the ER ( 9 ). On the basis of on our prior studies, we can rule out increases in lipid peroxides and reactive oxygen species as the mechanism for OA-induced ER stress ( 14 ).…”
Section: Dha But Not Oa or Pa Increases Autophagic Fl Ux In Mca Cellsmentioning
confidence: 80%
“…First, ER stress has been shown to stimulate de novo fatty acid synthesis in the liver, adding to the burden of excess fatty acid delivery to the liver (28)(29)(30). Second, ER stress reduces the secretion of apoB100 lipoproteins, interfering with the ability of hepatocytes to export the excess TG that has accumulated ( 6,9 ). TG itself does not appear to be the mediator of fatty acid-induced ER stress in the liver ( 31,32 ) and may instead constitute a neutral form of storage for fatty acids.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that delayed apoB-100 turnover may be the major cause of the ER stress in p97 knockdown cells. Indeed, it was recently proposed that overproduction of the apoB-100 protein may be a "molecular link" between lipidinduced ER stress and hepatic insulin resistance ( 37 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, we have previously shown that inhibition of fatty acid oxidation protects the liver from ER stress in vivo (56), suggesting that fatty acid catabolism contributes to ER stress. In addition, because lipogenesis occurs at the ER membrane, it also might compromise ER function and thus be targeted for suppression during UPR activation; at a minimum, triglyceride synthesis and production and secretion by the liver of VLDL lead to ER stress (57). It is conceivable that both anabolic and catabolic lipid fluxes tax the ER and that the UPR is primed to suppress both processes.…”
Section: Chopmentioning
confidence: 99%